Assessing Justice: Exploring the Role of Values in Defining Fairness - Subhan Ajrin Sudirman (Indonesian Center for Religion and Society Studies (InTReSt), 2022)
Assessments of justice can vary due to its dual objective and subjective dimensions. Objectively, justice can be achieved through the establishment of a distribution system that follows predetermined standards. However, subjective evaluations of justice can be influenced by psychological factors that differ among individuals. Many psychological factors influence an individual's assessment of a particular distribution system. This research aims to explore subjective assessments of justice by involving an individual's inherent factors, namely the value variable, while also examining the values inherent in each individual. As a result, personally-oriented values such as achievement, power, and hedonism have a correlation with procedural justice assessments and distributive justice assessments that are fair. Furthermore, collectively-oriented values such as virtue, universalism, and conformity also have a correlation with procedural justice assessments and distributive justice assessments that are fairly distributed.